2018
DOI: 10.1111/vsu.12913
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of three antiseptics as surgical skin preparations in dogs

Abstract: Objective To compare the antimicrobial efficacy of a 2% chlorhexidine gluconate and 70% ethanol solution (CG+A) with that of F10 Skin Prep Solution (F10) and electrochemically activated water (EAW) when used as a surgical preparation in canine patients. Study design Prospective randomized clinical study. Sample population One hundred sixteen dogs presented for ovariohysterectomy. Methods Dogs were randomly divided into 1 of the 3 antiseptic groups (CG+A, F10, EAW). Skin samples with replicating organism detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…Bacterial counts before skin preparation in this study were similar to or higher than those found in other canine studies, although different preparation solutions were used 12,13,28,35 . Bacterial reduction was not always complete.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Bacterial counts before skin preparation in this study were similar to or higher than those found in other canine studies, although different preparation solutions were used 12,13,28,35 . Bacterial reduction was not always complete.…”
Section: Discussionsupporting
confidence: 79%
“…Bacterial reduction was not always complete. Similar results have been observed in canine studies in which different preparation techniques were compared 12,28‐30,35 . We used a moist swab placed on the skin and rotated with firm pressure in contrast to the impression technique in which culture plates are gently pressed directly onto the skin.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…To position the intravenous catheter, the hair above the cephalic vein was removed. Subsequently, the skin was disinfected with three alternating passages of 4% chlorhexidine and denatured ethyl alcohol 70% (each left on for 30 s), following the main indications for skin antisepsis [18,19]. Once the area was ready, the intravenous catheter was positioned with the operator wearing sterile gloves.…”
Section: Methodsmentioning
confidence: 99%